Writing trauma : the voice of the witness in Rwandan women's testimonial literature - Gilbert, Catherine (2014)
During the 1994 genocide in Rwanda, acts of extreme violence were committed against women. This thesis aims to explore how Rwandan women genocide survivors respond to and communicate such a traumatic experience. From a perspective of trauma theory, it engages with the published testimonies of Rwandan women survivors, seeking to understand how the genocide is remembered in both individual and collective memory and the challenges Rwandan women face in the ongoing process of surviving trauma. Exploring the ways in which Rwandan women position themselves as witnesses, the first chapter addresses the crucial questions of who is a witness and who has the right to speak about a traumatic historical event. It distinguishes between different categories of witness and looks at the levels of witnessing in Rwandan women’s testimonies, as well as considering the role of the reader-witness in the act of testimony. Responding to an imperative of memory, the women are speaking on behalf of other survivors and honouring the memory of the victims. At the same time, the experience of genocide is shown to be deeply individual, and the second chapter provides a detailed analysis of the narrative strategies Rwandan women adopt to communicate the particularity of their experiences. Through a range of ‘translation’ techniques, the women reconstruct their individual chronologies and challenge the notion of the unsayability of trauma. However, the extremity of what the women have lived through can be incomprehensible to the reader, who is often unwilling to hear the story. One of the ways in which cross-cultural communication can be achieved is through collaboration, a process which is examined in the third chapter. The collaborator plays a complex role in the production of the testimonies, functioning not only as empathic listener, but also as writer, editor, and mediator of the story. This chapter draws out the problems associated with collaboration and also highlights its potential value for the Rwandan women as it is ultimately through the collaborator that they are able to convey their story to a Western audience. Gaining access to the Western publishing industry is just one of the many obstacles the women must face in communicating their stories, and the majority of survivors continue to be silenced. The role of silence both within and surrounding Rwandan women’s testimonies is the focus of the fourth chapter, which looks at the physical manifestations of silence within the narratives as well as the silencing of survivors in Rwanda and across the diaspora. The silencing of survivors’ stories has strong implications for the recovery of the individual, often preventing her from moving from surviving to living, a notion that is examined in the final chapter. Testimony is shown to play a central role in this transition. Yet, in the face of the politically motivated processes of national reconciliation, justice and commemoration, Rwandan women struggle to regain control over their narratives. This final chapter emphasises the importance of the community in helping women to reclaim their voice and tell their stories on their own terms. Overall, women remain marginalised figures in the writing of history, and this thesis seeks to underline the necessity of developing new ways of listening to the diversity of Rwandan women’s voices, in order not only to gain greater insight into how traumatised individuals remember but also to hear the challenge they pose to conventional Western modes of responding to trauma.